A new species of Chresta (Vernonieae, Asteraceae) endemic to the Mata Atlântica Domain, Brazil - Moriani Siniscalchi, Carolina; Francis Patrice Loeuille, Benoit; Pirani, José Rubens (Phytotaxa, 2016)
Chresta filicifolia is described and illustrated. It is a perennial herb known only from open vegetation on top of small rock outcrops at the Rio Doce Valley in Eastern Minas Gerais, Southeastern Brazil. This is the first record of a species of Chresta endemic to a phytogeographic domain other than the Cerrado and Caatinga, since those outcrops are included in the Mata Atlântica Domain (Atlantic Forest). The new species is closely related to C. harleyi and C. hatschbachii, but differs from these by its leaves, which are larger and more deeply lobed than those of the other two species, and also by its florets and cypselae, which are both larger in Chresta filicifolia. Moreover, the two other species are allopatric from C. filicifolia, being restricted to the Caatinga Domain. The southernmost distribution of C. harleyi lies more than 500 km away from the locality where the new species is found, making this discovery unexpected, and raising interesting biogeographical questions, which are briefly addressed here.